TERORISME DALAM BINGKAI MEDIA MASSA - Dikhorir Afnan (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2018)
The phenomenon of terrorism in Indonesia in the past decade has attracted publicattention, both nationally and internationally. There are those who react to it as usual, butsome also assume based on political, religious, social and ideological perspectives. As astrategic information tool, mass media is very likely to construct reality on the ground intoa news product that not only has business value, but is also loaded with the interests of themedia ideology itself. In the context of Communication Science, to describe the process ofselecting and highlighting specific aspects of reality in journalistic products, the analysisof framing (framing) can represent traditions that prioritize a multidisciplinary approachor perspective to analyze phenomena or communication activities.Keywords: Terrorism, Framing, Mass Media